If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9b + 3 + 7b = 3b + 8 Reorder the terms: 3 + -9b + 7b = 3b + 8 Combine like terms: -9b + 7b = -2b 3 + -2b = 3b + 8 Reorder the terms: 3 + -2b = 8 + 3b Solving 3 + -2b = 8 + 3b Solving for variable 'b'. Move all terms containing b to the left, all other terms to the right. Add '-3b' to each side of the equation. 3 + -2b + -3b = 8 + 3b + -3b Combine like terms: -2b + -3b = -5b 3 + -5b = 8 + 3b + -3b Combine like terms: 3b + -3b = 0 3 + -5b = 8 + 0 3 + -5b = 8 Add '-3' to each side of the equation. 3 + -3 + -5b = 8 + -3 Combine like terms: 3 + -3 = 0 0 + -5b = 8 + -3 -5b = 8 + -3 Combine like terms: 8 + -3 = 5 -5b = 5 Divide each side by '-5'. b = -1 Simplifying b = -1
| y=96t-16t^2 | | 2(x-1)-7=5 | | 2-5x=12+7x | | 10+4(x+1)+5= | | 5(x-3)+4=20 | | 3+5q=q+4 | | 2x-9+9x=-28+10 | | x+x=84+8 | | y=36x-12x-18 | | 5=7x-3 | | 5=5x-3 | | 6x=30-2x | | 5=3x-3 | | 15(2+4x)-35x=3x+2 | | 5=4x-3(1-x) | | x-8=9+x | | 7x-2=x+16 | | h(x)=(3a^4)+8(3a^2)+5 | | 6x+5=2x+27 | | 5(x-3)+4=24 | | x^2-6x+q=0 | | 6x+5=3x+27 | | 56+12x=80+12x | | 12s+4s-10=22 | | 2(6x-1)-(x-7)= | | 2x-9+7x=-28+10 | | 30+3x=87 | | 10y+12=3y+54 | | 4y+3[(x-5y)-(6-y)]= | | 2x^2=23x | | -47=3x-50 | | 3x+12=6x+33 |